Zinc-Catalyzed Alkyne Oxidation/CH Functionalization: Highly Site-Selective Synthesis of Versatile Isoquinolones and β-Carbolines - Li, Long; Zhou, Bo; Wang, Yong-Heng; Shu, Chao; Pan, Yi-Fei; Lu, Xin; Ye, Long-Wu (Angewandte Chemie International Edition, 2015)
An efficient zinc(II)‐catalyzed alkyne oxidation/CH functionalization sequence was developed, thus leading to highly site‐selective synthesis of a variety of isoquinolones and β‐carbolines. Importantly, in contrast to the well‐established gold‐catalyzed intermolecular alkyne oxidation, over‐oxidation can be completely suppressed in this system and the reaction most likely proceeds by a Friedel–Crafts‐type pathway. Mechanistic studies and theoretical calculations are described. Swap gold for zinc: The title reaction was achieved by a zinc(II)‐catalyzed alkyne oxidation/CH functionalization sequence. In contrast to the well‐established gold‐catalyzed intermolecular alkyne oxidation, the over‐oxidation can be suppressed in this system and the reaction most likely proceeds by a Friedel–Crafts‐type pathway. Tf=trifluoromethanesulfonyl, PG=protecting group.